Genetic variants in RORA are associated with asthma and allergy markers in an admixed population. (January 2019) - Lima, Louise Correia; Queiroz, Gerson de Almeida; Costa, Ryan dos Santos; Alcantara-Neves, Neuza Maria; Marques, Cíntia Rodrigues; Costa, Gustavo Nunes de Oliveira; Barreto, Mauricio Lima; Figueiredo, Camila Alexandrina Viana; Carneiro, Valdirene Leão
Highlights: RORA SNVs are associated with atopic and non-atopic asthma in an admixed population. Haplotypes in RORA gene are associated with atopic sensitization. IL-13 production by dust mite stimulus is associated with RORA SNV. The G allele of rs17191519 is associated with IL-5 production in atopic individuals. Abstract: Asthma and allergy affect hundreds of millions of people from childhood to old age. In most of them, the inflammatory process of respiratory allergies involves the participation of type 2 cytokines, derived from T helper-2 (Th2)-cell, and Group 2 Innate Lymphoid (ILC2) Cells. An efficient memory Th2 cell response is dependent on IL-13 produced by ILC2s, causing allergic lung inflammation and elevated serum levels of immunoglobulin E. ILC2 cells are derived from common lymphoid progenitors and their growing depends on the transcription factor RORA. The aim of this work was to identify genetic variants in RORA associated with asthma phenotypes and allergy markers. Genomic DNA samples of 1246 individuals participating from Social Changes Asthma and Allergy in Latin America Program (SCAALA) have been genotyped using Illumina Human 2.5 Omni Beadchip. Logistics regressions have been performed to analyze the association among RORA variants and asthma, skin prick tests (SPT), specific IgE and type 2 cytokine production. Twelve single nucleotide variants (SNVs) were significantly associated with atopy (P < 0.01), in which four of them, rs10162630, rs17191519, rs17270243, and rs55796775 and their haplotypes were strongly and positively associated (P < 0.001). Furthermore, these variants increased the RORA gene expression in silico analysis. Other SNVs in RORA were associated with allergy markers, atopic and non-atopic asthma. Therefore, it is believed that variants in RORA gene may influence immunologic features of asthma and allergies and could be possible targets for future treatment of allergic diseases.